2022
DOI: 10.1186/s12906-022-03764-1
|View full text |Cite
|
Sign up to set email alerts
|

Baduanjin exercise for balance function in community-dwelling older adults with cognitive frailty: a randomized controlled trial protocol

Abstract: Background Balance function provides a physiological link between the physical and cognitive function, and is a potential predictor for cognitive frailty. As a gentle mind–body exercise, Baduanjin can develop flexibility and co-ordination, thus would be is helpful for the improvement of balance function. This trial will evaluate the effect of Baduanjin on balance function in older adults with CF. Methods/design A total of 72 community-dwelling olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Problems with dynamic balance are associated with aging in different physiological systems, such as the muscular, nervous, sensory, and vestibular systems, and good communication between these systems is required to maintain balance and postural control. Balance is, therefore, a physical and cognitive health parameter ( 43 ). Furthermore, impaired dynamic balance has been shown to be very closely associated with falls in older adults ( 44 ), and an earlier study found that altered results in a test known as dynamic posturography during a dual-task protocol were associated with pre-frailty and frailty in older adults ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Problems with dynamic balance are associated with aging in different physiological systems, such as the muscular, nervous, sensory, and vestibular systems, and good communication between these systems is required to maintain balance and postural control. Balance is, therefore, a physical and cognitive health parameter ( 43 ). Furthermore, impaired dynamic balance has been shown to be very closely associated with falls in older adults ( 44 ), and an earlier study found that altered results in a test known as dynamic posturography during a dual-task protocol were associated with pre-frailty and frailty in older adults ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The sample size for each arm was calculated using the statistical power of G Power [37] with 80% power and an alpha of 0.05. effect size type I error (two-tailed); at least 30 subjects in each group were sufficient [38]. Considering a 20% dropout rate, 35…”
Section: Sample Sizementioning
confidence: 99%